Comparison of Ceftriaxone Plus Weekly Azithromycin or Daily Ofloxacin for Outpatient Treatment of Pelvic Inflammatory Disease: a randomized clinical trial - Parisa Moghtadaei; Fariba Sardari; Sedigheh Esmaeilian (Tehran University of Medical Sciences, 2008)
Objective: To compare the efficacy of ceftriaxone plus Ofloxacin or Azithromycin for cases of pelvic inflammatory disease (PID). Materials and Methods:  This clinical terial was performed on 180 women with PID from March 2005 to March 2007 in Parastarane-Shahed Hospital. Patients with PID were randomly divided to receive injection of Ceftriaxone 250 mg plus Ofloxacin 200 mg per day or Azithromycin 1 g per week for two weeks (90 cases in each group). The degree of pain was assessed on days 7, 14, 30 and clinical cure was assessed on days 14 and 30. Statistical analysis was done based on Fisher exact test, Mann-Whitny and student t-test. Results: From 180 patients eligible for the study, 138 cases were enrolled for protocol analysis. Significant differences were observed regarding the degree of pain between two groups. Clinical cure was 90% (70 of 78) for Azithromycin and 83.3% (50 of 60) for Ofloxacin. Conclusion: Combination of Ceftriaxone plus weekly Azithromycin for two weeks is not only equivalent to Ceftriaxone plus daily Ofloxacin for two weeks but also seems to be better for the treatment of mild PID.